Dental and oral health assessments in the German National Cohort (NAKO) - Samietz, Stefanie A.; Borof, Katrin; Hertrampf, Katrin; Aarabi, Ghazal; Ciardo, Antonio; Finke, Hannah; Hagenfeld, Daniel; Kühnisch, Jan; Rütters, Maurice; Baumeister, Sebastian E.; Reckelkamm, Stefan Lars; Kim, Ti-Sun; et al. (BMC oral health, 2025)
Despite considerable improvements in oral health in recent decades, caries and periodontitis are still widespread, ranking among the most prevalent diseases worldwide and requiring future research. The German National Cohort (NAKO Gesundheitsstudie, NAKO) is a large-scaled, multidisciplinary, nationwide, multi-centre, population-based, prospective cohort study with oral examinations that aims to provide a resource to study risk factors for major diseases. The aim of the present article is to provide the methodological background, to report on the data quality, and to present initial results of the oral examinations.
Gesehen am 06.11.2025